Obtención De Alcohol A Partir De Remolacha - Hanníbal, Brito; Valeria, Tapia; José, Usiña; Horacio, Guamán; César, Puente; Teobaldo, Patiño; Mery, Mendoza; Carla, Haro; Beatriz, Moreno (European Scientific Journal, ESJ, 2016)
The preparation of beet alcohol by fermentation and distillation processes, has as a main objective is to obtain alcohol with purity in excess of 90 %, In order to accomplish this goal, initially we proceeded with a market sampling including Mayorista, La Condamine, La Merced, San Alfonso and La Esperanza markets in the city of Riobamba. Beet samples were taken in each of them and they were analyzed in the laboratory of industrial processes at the Polytechnic School of Chimborazo (ESPOCH). It was identified that the optimal beet for the fermentation process is the one collected at Mayorista market. It meets the highest percentage of solids with a 13,66 % among the analyzed. Using the beet from Mayorista market, the amount of juice and water suitable for the preparation of 100 L of must was determined. Yeast dissolved in water and ammonium sulfate were to the mixture, after which, the reactor was sealed to start the fermentation process: Temperature and time variables were adjusted, later samples were taken every hour until achieving constant alcoholic strength, which was 12 % in a time span of 12 hours. The ensuing product was fed to the distillation tower until reaching the 94 % alcohol at a boiling temperature of 76 °C. Optimum process variables required in the fermentation process are: T =30 ° C, pH = 4,3 and in the process of distillation; a boiling temperature of 76 ° C to reach an alcohol content of 94 %.